(3SDGd aj GdbOQ eY GdLhGH hGdGYJQGV Ydjgs - (3aQL Hf bGSe Hf CMeO Hf dH GdJZdHj GdZQfGWj, GHf dH , CHh SYjO,J (B782 (3g` s
(3ChdgG (B:s
(3GdSDGd CjG YdeGA GdOjf Pei Ojfce JMjQ Pdhg HChVM MLI EPG eG bVi QHi HcaQi HRYece hde jQVg efi aeG hLg MjdJi s
(3BNQgG (B:s
(3hBd hUMH CLeYjf hJGHY hJGHYge eUMhHI HGdJMjI LhGHc ef fLd GdJHS eQTO hef hGgH GdJhajb bhdi aadJi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdSDGd ai GdbOQ dMHQ jghOis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B58s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs